2021
DOI: 10.34172/ajcmi.2021.10
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Zinc Oxide Nanoparticles on Loaded Antibiotics Against Multidrug-Resistant Acinetobacter spp.

Abstract: Background: Metal oxide nanoparticles (NPs) have shown promising efficacy for combating bacterial resistance due to their antibacterial properties. This research investigated the effect of zinc oxide NPs (ZnO-NPs) on the antibacterial activity of conventional antibiotics including ciprofloxacin (CIP), cefotaxime (CTX), and colistin (CST) against multidrug-resistant Acinetobacter isolates. Methods: The disc diffusion method was performed to detect the pattern of antibiotic resistance in isolates. The synthesize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 17 publications
1
2
1
Order By: Relevance
“…In terms of biofilm production power, like other studies, all the isolates were not able to produce biofilm [ 25 – 27 ]. In the investigations carried out in Iran by Shokrollahiet al and the study conducted by Łysakowska et al in Poland, contrary to the present study, they showed that there is a significant relationship between MIC of nanoparticles and antibiotic resistance [ 28 , 29 ]. In the study conducted by Hendiani et al in Iran, like the study conducted in other parts of the world, in line with the present study, they concluded that there is a significant relationship between the power of biofilm production and the MIC of Ag and ZnO NPs [ 30 – 32 ].…”
Section: Discussioncontrasting
confidence: 95%
“…In terms of biofilm production power, like other studies, all the isolates were not able to produce biofilm [ 25 – 27 ]. In the investigations carried out in Iran by Shokrollahiet al and the study conducted by Łysakowska et al in Poland, contrary to the present study, they showed that there is a significant relationship between MIC of nanoparticles and antibiotic resistance [ 28 , 29 ]. In the study conducted by Hendiani et al in Iran, like the study conducted in other parts of the world, in line with the present study, they concluded that there is a significant relationship between the power of biofilm production and the MIC of Ag and ZnO NPs [ 30 – 32 ].…”
Section: Discussioncontrasting
confidence: 95%
“…The antibacterial sensitivity test results in this study indicate the widespread resistance among A. baumannii isolates against most commonly used antibacterial agents in Firoozgar Hospital, Tehran, Iran, so that 77.14% of the isolates were found resistant to cefepime. MDR patterns of A. baumannii reported here was similar to the one have been reported previously in many parts of the world [37–39]. Our data showed significant correlations between the presence of HicA/HicB system and resistance to ceftazidime, meropenem, imipenem, and cefepime ( p < 0.05), and the presence of HipA/HipB system and resistance to ceftazidime, meropenem, imipenem, and cefepime.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, we report that the treatment of MDR A. baumannii with a subinhibitory concentration of ZnO‐NPs resulted in reduction in expression of all studied genes ( GNAT and hicB showed the highest and lowest rate change of expression by 2.4 folds ( p < 0.001) and 1.3 folds ( p < 0.05), respectively). The antimicrobial effect of ZnO‐NPs alone [38, 39, 44, 45] and its synergistic effect in combination with antibiotics [38, 39] against resistant Acinetobacter has been demonstrated in previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…In studies on different bacteria, including S. aureus and E. coli, ZnO-NPs (20-45 nm) combined with various antibiotics demonstrated variable impacts on bacterial resistance [27,28]. Other studies in Iran have also revealed the ability of ZnO-NP to enhance the antimicrobial actions of fluoroquinolones (ciprofloxacin) and cephalosporins (ceftazidime) against MDR A. baumannii [23,29]. Moreover, the sub-inhibitory concentration of ZnO-NPs did not affect the activity of ciprofloxacin against A. baumannii but enhanced ceftazidime activity [30].…”
Section: Discussionmentioning
confidence: 99%